Architectural shop drawing of SF11-SF12 of 8th & 9th storey (RFA- 032_Rev-A) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.